P172 Time Trends in Incidence and Prevalence of Bronchiectasis in the UK. (19th November 2012) - Quint, JK; Millett, E; Hurst, JR; Smeeth, L; Brown, J
Abstract : Background: The incidence of bronchiectasis in the UK is unknown. No large study has been performed in the UK since the 1950s 1 and there are few relevant data from non-UK sources. The prevalence is likely to be relatively high as bronchiectasis is a chronic condition, and case ascertainment is increasing with the wider availability of CT scanning. Establishing the healthcare burden is essential for informing allocation of healthcare resources and improving patient experience. Methods: All individuals in the general practise research database (CPRD-GOLD) between 1st January 2004 and 31stDecember 2011 were included. Currently this includes information from 640General Practises in the UK. From this cohort, patients with a diagnosis of bronchiectasis were identified using specific READ codes. We calculated the absolute incidence rates and prevalence of bronchiectasis by calendar year, age and gender. Results: Over the 8 year time period 27, 258 individuals (0.7%) had a diagnosis of bronchiectasis. The overall incidence increased overtime; 2004 incidence 18/100, 000 person years at risk and in 2011 the incidence was 32/100, 000 person years at risk. Prevalence also increased year on year, was higher in older age groups (> 60 years of age) and was higher in women than in men. The prevalence in 2011 in men and women by age is provided in Table 1 . Conclusions: Bronchiectasis is a relatively common condition in 2011 in the UK, particularly in individuals over the age of 60. Part of the increase in prevalence over time may be due to increasing numbers of CT scans being performed. How the prevalence relates to individual disease burden and health careutilisation is yet to be established. References: Guideline for non-CF Bronchiectasis, British Thoracic Society (July 2010).